Odpowiedź:
9. a)
W(x) = ( 5 x)³ - 2³ = ( 5 x -2)*(25 x² + 10 x + 4)
Δ = 100 - 4*25* 4 < 0
5 x - 2 = 0
5 x = 3
x = 0,6 - p. jednokrotny
--------------------------------
a³ - b³ = ( a - b)*( a² + a b + b²)
b) W(x) = 9 x*( x² - 3) - 4*( x² - 3) = ( x² - 3)*( 9 x - 4) =
= ( x - √3)*(x + √3)*(9 x - 4)
-------------------------------------------
x = √3 x = - √3 x = [tex]\frac{4}{9}[/tex] - pierwiastki jednokrotne
============================
c) W(x) = 6 x² *( x² -2 x + 1) = 6 x² *( x - 1)²
x = 0 - p. podwójny
x = 1 - p. podwójny
========================
z. 1o
W(x) = 2 [tex]x^4 -3 x^2 + a x + a^2 x + 2[/tex]
R = W( 1) = 2 - 3 + a + a² + 2 = a² + a + 1
R > 3 ⇔ a² + a + 1 > 3 ⇔ a² + a - 2 > 0 ⇔ ( a + 2)*( a - 1) >0 ⇔
⇔ a ∈ ( - ∞ , - 2) ∪ ( 1, +∞ )
============================
Szczegółowe wyjaśnienie: